The Effect of an Aerobic Exercise Program, Massage and a Combined Protocol on Premenstrual Syndrome - lila Ghaedi; mohammadhossin Alizadeh; Tourandokht Aminian Razavi (Sport Sciences and Health Research)
The aim of the present study was to examine the effect of an aerobic exercise, massage and a combined protocol on premenstrual syndrome (PMS) of non – athletic female students. 60 non–athletic university students with the primary diagnosis of PMS voluntarily participated in this study. Subjects were randomly divided into four groups called aerobic exercise, massage, combined and control group. Variables were measured by the criteria of PMS (DSM – IV). Data were analyzed by descriptive and analytic statistics (paired T test, one-way ANOVA and LSD). As a results, the comparison of pretest and posttest showed that somatic symptoms significantly decreased in all four groups (P